Alpha-Toxin Promotes Staphylococcus aureus Mucosal Biofilm Formation - Anderson, Michele J.; Lin, Ying-Chi; Gillman, Aaron N.; Parks, Partick J.; Schlievert, Patrick M.; Peterson, Marnie (Frontiers in Cellular and Infection Microbiology, 2012)
Staphylococcus aureus causes numerous diseases in humans ranging from the mild skin infections to serious, life-threatening, superantigen-mediated Toxic Shock Syndrome (TSS). S. aureus may also be asymptomatically carried in the anterior nares, vagina or on the skin, which serve as reservoirs for infection. Pulsed-field gel electrophoresis clonal type USA200 is the most widely disseminated colonizer and a major cause of TSS. Our prior studies indicated that α-toxin was a major epithelial proinflammatory exotoxin produced by TSS S. aureus USA200 isolates. It also facilitated the penetration of TSS Toxin-1 (TSST-1) across vaginal mucosa. However, the majority of menstrual TSS isolates produce low α-toxin due to a nonsense point mutation at codon 113, designated hly, suggesting mucosal adaptation. The aim of this study was to characterize the differences between TSS USA200 strains [high (hla+) and low (hly+) α-toxin producers] in their abilities to infect and disrupt vaginal mucosal tissue. A mucosal model was developed using ex vivo porcine vaginal mucosa, LIVE/DEAD® staining and confocal microscropy to characterize biofilm formation and tissue viability of TSS USA 200 isolates CDC587 and MN8, which contain the α-toxin pseudogene (hly), MNPE (hla+) and MNPE isogenic hla knockout (hlaKO). All TSS strains grew to similar bacterial densities (1-5 x 108 CFU) on the mucosa and were proinflammatory over 3 days. However, MNPE formed biofilms with significant reductions in the mucosal viability whereas neither CDC587, MN8 (hly+), or MNPE hlaKO, formed biofilms and were less cytotoxic. The addition of exogenous, purified α-toxin to MNPE hlaKO restored the biofilm phenotype. Our studies suggest α-toxin affects S. aureus phenotypic growth on vaginal mucosa, by promoting tissue disruption and biofilm formation; and α–toxin mutants (hly) are not benign colonizers, but rather form a different type of infection, which we have termed high density pathogenic variants (HDPV).